Simulations of the isochronous mass spectrometry at the HIRFL-CSR. (26th November 2015) - Chen, R J; Yuan, Y J; Wang, M; Xu, X; Shuai, P; Zhang, Y H; Yan, X L; Xing, Y M; Xu, H S; Zhou, X H; Livinov, Y A; Litvinov, S; et al.
Abstract: A Monte-Carlo simulation code, named as SimCSR, has been developed for the isochronous mass spectrometry experiments in the experimental storage ring (CSRe). The revolution times of the fragments ions stored in the CSRe, which were produced in the fragmentation of primary beam are reproduced very well by the SimCSR, although only linear components are considered. The standard deviation of the revolution time is found to be strongly affected by the phase slip factor, the width of the relative momentum difference and the instability of magnetic field. Based on the simulations, we outline and discuss the methods to reduce the standard deviation of the revolution time.